Coronary Artery Disease: An emerging Epidemic in Nepal - Maskey, Arun; Sayami, Arun; Pandey, Mrigendra Raj (Nepalese Heart Journal, 2003)
Cardiovascular diseases (CVD) accounts for approximately 12 millions deaths annually and is the commonest cause of death globally, CVD is also the major contributor to the burden of premature morbidity and mortality and accounted for 85 millions disability adjusted (DALY) life years In 1990. It has been estimated that during the 25 years period from 1965-1990 mortality from coronary artery diseases (CAD) fell by 50% in Australia, Canada, France & US and 60% in Japan and Finland. The identification of major risk factors and effective control of them through population-based strategies of prevention were mainly responsible for this decline. The rise and subsequent decline in CAD epidemic in almost all industrialized countries in the later half of twentieth century has been well documented, but most of the developing countries are experiencing alarming increase of the disease.